2015
DOI: 10.1128/jvi.01437-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATM in the Formation of the Replication Compartment during Lytic Replication of Epstein-Barr Virus in Nasopharyngeal Epithelial Cells

Abstract: Epstein-Barr virus (EBV), a type of oncogenic herpesvirus, is associated with human malignancies. Previous studies have shown that lytic reactivation of EBV in latently infected cells induces an ATM-dependent DNA damage response (DDR).The involvement of ATM activation has been implicated in inducing viral lytic gene transcription to promote lytic reactivation. Its contribution to the formation of a replication compartment during lytic reactivation of EBV remains poorly defined. In this study, the role of ATM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 68 publications
8
40
1
Order By: Relevance
“…However, the involvement of cellular pathways in mediating lytic induction seems to be varying in different cell types and upon treatment with different stimuli. For instance, although the ATM pathway was shown to be crucial for the regulation of EBV lytic cycle reactivation, other findings have also suggested that ATM was only involved in the stage of viral DNA replication rather than the initial step of lytic reactivation . Our data seem to support the latter argument because ATM inhibitor did not abrogate the lytic cycle reactivation by romidepsin in both NPC and GC cell lines in our study (refer to Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, the involvement of cellular pathways in mediating lytic induction seems to be varying in different cell types and upon treatment with different stimuli. For instance, although the ATM pathway was shown to be crucial for the regulation of EBV lytic cycle reactivation, other findings have also suggested that ATM was only involved in the stage of viral DNA replication rather than the initial step of lytic reactivation . Our data seem to support the latter argument because ATM inhibitor did not abrogate the lytic cycle reactivation by romidepsin in both NPC and GC cell lines in our study (refer to Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Conceivably, lytic viral proteins, such as BZLF1 or BGLF4, may promote the late activation of ATM to enhance EBV replication through induction of cell cycle arrest and the assembly of replication compartments that are regulated by the kinase. 38 In line with the notion that SP1 regulates the BZLF1 promoter, we found that the effects of TPA/Bu and DNA damage converge on activation of this cellular transcription factor. SP1 may serve both as transcriptional repressor and activator depending on the recruitment of HDAC-containing repressor complexes.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, the phosphorylation of ATM and H2AX observed in cells exposed to TPA/Bu for 24 hr was not associated with activation of a canonical DDR, as assessed by failure to detect ubiquitination of H2AX, phosphorylation of KAP1 and p53, and expression of p21. Conceivably, lytic viral proteins, such as BZLF1 or BGLF4, may promote the late activation of ATM to enhance EBV replication through induction of cell cycle arrest and the assembly of replication compartments that are regulated by the kinase . In line with the notion that SP1 regulates the BZLF1 promoter, we found that the effects of TPA/Bu and DNA damage converge on activation of this cellular transcription factor.…”
Section: Discussionsupporting
confidence: 79%
“…In vitro EBV re-infection in nasopharyngeal epithelial cells has been able to suppress endogenous ATM expression and, sequentially, ATM kinase activity followed by exposure to IR [23]. The indispensable role of ATM in viral replication was also demonstrated in our recent study [24]. However, the involvement of EBV in ATM regulation has remained elusive and needs further investigation.…”
Section: Introductionmentioning
confidence: 51%
“…We have previously demonstrated that the ATM protein is consistently downregulated in EBV‐positive NPC and contributes to viral replication during EBV lytic reactivation in epithelial cells . Based on these findings, we hypothesize that the highly expressed miR‐BARTs are responsible for ATM regulation and subsequently inhibiting EBV lytic reactivation in NPC cells.…”
Section: Resultsmentioning
confidence: 82%